Modeling for Tansformer Condition Monitoring Using IoT: Temperature and Oil Level Parameters - Anisha Ningrum Julitasari; Umi Fadlilah (Universitas Muhammadiyah Surakarta, 2025)
Distribution transformer are important components in electrical system, functioning to reduce voltage from the transmission network to end users. Damage to transformeris often caused by unmonitored operations such as high temperature, low oil lvels, and trapped gas, which can disrupt the stability of the power system. Therefore, a monitoring device is needed to maintain the transformer so that it can provide maximum output, reduce the risk of failure, and extend the operational life of the transformer. This study uses a DS18B20 sensor and a VL53L0X sensor, with the DS18B20 sensor reading temperature parameters and the VL53L0X sensor measuring oil level parameters. The DS18B20 and Vl53L0X sensors are controlled by ESP32 and serve as centralized connectivity connected to Blynk. Furthermor, the Internet of Things (IoT) platform will display temperature and oil level parameters from both sensors in real time. This research produced a fairly good system. There was no difference between the readings on the LCD and the Blynk application, and indicators such as LEDs and Buzzers worked well. When the temperature or oil level exceeded the threshold, which was 4 cm for oil level and 50°C for temperature, not only did the indicators turn on, but the relay also turned on. This, it is hoped that the development of this tool can assist in monitoring transformer to extend their lifespan, thereby maximizing transformer productivity.